Human Resource Management in Islamic Education - Irja Eka Putri; Junaidi Junaidi (Early Publishing, 2026)
This study aims to analyze the implementation of human resource management (HRM) in Islamic educational institutions and its impact on stakeholder satisfaction. The research focuses on key HRM aspects, including planning, recruitment, development, and performance evaluation, as well as the challenges faced in their implementation. A qualitative descriptive approach was employed to gain an in-depth understanding of HRM practices from the perspectives of educators, administrative staff, and institutional leaders. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that HRM practices in Islamic educational institutions are generally effective, particularly in planning and development, which contribute positively to institutional performance. However, recruitment and performance evaluation remain areas that require improvement due to the lack of systematic and competency-based approaches. The study also finds that effective HRM is closely related to stakeholder satisfaction, as institutions with better HRM practices tend to achieve higher levels of trust and perceived service quality. Furthermore, this study highlights the importance of integrating managerial competence with Islamic values such as trustworthiness and ethical responsibility. This integration distinguishes HRM in Islamic education from conventional models and provides a more holistic framework for managing human resources. The results suggest that improving HRM through continuous evaluation, strategic recruitment, and comprehensive development programs is essential for enhancing educational quality. This study contributes to the development of a value-based HRM model that supports both professional excellence and moral integrity in Islamic educational institutions.